2004
DOI: 10.2519/jospt.2004.34.6.317
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Forefoot and Arch Posting Orthotic Designs on First Metatarsophalangeal Joint Kinematics During Gait

Abstract: Study Design: Repeated-measures analysis of variance. Objective: To examine the effect of 2 different orthotic posting designs on first metatarsophalangeal (first MTP) joint kinematics during gait. Background: Common orthotic designs used to control abnormal pronation incorporate the use of a medial post in the forefoot and/or rearfoot locations. Although this design may favorably alter rearfoot and lower-limb kinematics, the incorporation of a forefoot post has been theorized to negatively impact first MTP jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 46 publications
3
18
1
Order By: Relevance
“…The results from this study revealed that peak everted position values of RFM in the type A insole and type B insole (2.89±3.10° and 2.70±2.40°, respectively) in the longitudinal axis was significantly smaller than that of the normal insole (5.40±4.10°) (Table 2). This result was consistent with the findings of previous studies [3942], which reported that the peak rearfoot eversion was significantly reduced with a medial forefoot and rearfoot posting insole inserted to the foot. Also, the forefoot adduction (1.6°) was made by the functional insole [43], resulting in a decrease forefoot pronation which could positively have an effect on the everted position of rearfoot in patients with flatfoot [44].…”
Section: Discussionsupporting
confidence: 93%
“…The results from this study revealed that peak everted position values of RFM in the type A insole and type B insole (2.89±3.10° and 2.70±2.40°, respectively) in the longitudinal axis was significantly smaller than that of the normal insole (5.40±4.10°) (Table 2). This result was consistent with the findings of previous studies [3942], which reported that the peak rearfoot eversion was significantly reduced with a medial forefoot and rearfoot posting insole inserted to the foot. Also, the forefoot adduction (1.6°) was made by the functional insole [43], resulting in a decrease forefoot pronation which could positively have an effect on the everted position of rearfoot in patients with flatfoot [44].…”
Section: Discussionsupporting
confidence: 93%
“…Using this type of orthoses, Kilmartin et al 30 failed to improve the extension of the hallux either in HL patients or in healthy participants, but Munuera et al 31 achieved an improvement of 8° after 5 months of treatment in patients of ages from 25 to 32 years. According to Nawoczenski and Ludewig, 32 control of pronation and increasing the medial longitudinal arch of the foot did not imply any improvement in the range of dorsiflexion of the hallux. One of the conclusions drawn in that study was that the degree of plantarflexion of the first metatarsal is directly proportional to the dorsiflexion of the hallux, thus coinciding with the purpose of our first measurement (relaxed position of the first MPJ).…”
Section: Discussionmentioning
confidence: 92%
“…Participants were excluded if they had established hallux valgus, a previous history of foot and ankle trauma, fracture, surgery, or an existing diagnosis of inflammatory, metabolic, neurological, or vascular disease. Individuals were also excluded from the study if they exhibited less than 40° of available first MTP joint dorsiflexion (as measured using a nonweight-bearing technique previously described by Buell et al 9 This has been reported to be the range of first MTP joint dorsiflexion used during normal propulsion 10 12 and would, therefore, have indicated structural limitation at the joint. In addition, no subject had a history of congenital deformity, pain, or traumatic injury involving either of their lower extremities during the 6 months prior to study enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…Push off was defined as the period of gait between heel off and toe off, which was the time when peak dorsiflexion of the first MTP joint and metatarsal declination angle due to plantarflexion at first metatarsal cuneiform joint occurred in the three planes. 11…”
Section: Methodsmentioning
confidence: 99%